The effects of exclusive on-street carsharing parking on carsharing perception and car ownership: A structural equation modeling approach - Felix Czarnetzki (Journal of Transport and Land Use)
Carsharing is considered an effective tool for reducing car ownership, especially in high-density urban areas. Dedicated on-street carsharing parking spaces (CPS) are a promising but under-researched approach to increase the attractiveness and impact of carsharing. Since 2017, Hamburg, Germany, has focused on providing small clusters of such carsharing parking spaces in inner-city residential neighborhoods. This paper is based on survey data of users of these parking spaces. A structural equation model is applied to examine the effects of exclusive carsharing parking spaces on the perception of carsharing as well as on car ownership of carsharing users. The results confirm that the provision of exclusive and conveniently accessible carsharing parking spaces promotes the perception of carsharing as a viable substitute for private cars, which ultimately leads to lower actual car ownership. However, perceived usability constraints of these facilities, such as long access distances or parking violations, lead to significant losses in their effectiveness.